2021
DOI: 10.32894/kjms.2021.170173
|View full text |Cite
|
Sign up to set email alerts
|

Association of Right Ventricular Infarction With Inferior Wall Myocardial Infarction

Abstract: Background:The right ventricular infarction occurs frequently in association with inferior myocardial infarction and occurs separately in rare patterns. It is related to higher morbidity and mortality rates. Aim of study:To measure the prevalence of right ventricular infarction among patients with inferior wall myocardial infarction and identifying the characteristics related to right ventricular infarction. Patients and methods: A cross sectional study carried out in CoronaryCare Unit of Azadi Teaching hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Stratification shows that age, gender, and duration of symptoms had no significant impact on right ventricular infarction, while diabetes mellitus (P=.046) and hypertension (P=.044) had a significant association with the incidence of right ventricular infarction. The effect of study variables right ventricular infarction in patients with inferior wall MI is shown in (Aziz, 2021); these findings were consistent with the results of the current study. Another study reported the frequency of right ventricular infarction to be 37.5%; it was also found that second and thirddegree heart block increases morbidity in those with inferior wall MI.…”
Section: Resultssupporting
confidence: 92%
“…Stratification shows that age, gender, and duration of symptoms had no significant impact on right ventricular infarction, while diabetes mellitus (P=.046) and hypertension (P=.044) had a significant association with the incidence of right ventricular infarction. The effect of study variables right ventricular infarction in patients with inferior wall MI is shown in (Aziz, 2021); these findings were consistent with the results of the current study. Another study reported the frequency of right ventricular infarction to be 37.5%; it was also found that second and thirddegree heart block increases morbidity in those with inferior wall MI.…”
Section: Resultssupporting
confidence: 92%